Meningkatkan Hasil Belajar Siswa Dalam Pembelajaran Matematika Materi Satuan Panjang Melalui Media Tangga Pintar Satuan Panjang - Maulidiyah, Richa Alfina; Setyawan, Agung (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
The research entitled "Improving Student Learning Outcomes in Mathematics Learning Unit Length Material Through Learning Media Unit Length Smart Stairs in Class IV SDN Kuluran" aims to find out whether the unit length smart ladder learning media can improve student learning outcomes in mathematics lesson unit length material. This research was compiled using classroom action research methods, the research subjects were fourth grade students at SDN Kuluran consisting of 13 students. Data collection through documentation, observation and interviews.